CASE REPORT: OS FEMORAL AND OS TIBIAL DIAPHYSIS FRACTURE ON LOCAL DOG - Witoko, Maria Clafita; Wirata, I Wayan; Wardhita, Anak Agung Jaya (Journal of Veterinary and Animal Sciences; Vol 4 No 2 (2021)DO - 10.24843/JVAS.2021.v04.i02.p05, 2021)
Abstract. The purpose of this study was to determine the open reduction internal fixation on femoral and tibial diaphysis oblique fractures on a local dog. A physical, hematological, and radiography examinations had been conducted on a 7-months-old female dog, weighing 8 kg at the Animal Educational Hospital, Faculty of Veterinary Medicine, Udayana University. Based on the result of the examinations, the animal was diagnosed with sinister caudal extremity femoral and tibial diaphysis oblique fractures with fausta prognosis. Open reduction surgery was conducted to return the fractured bones back to its normal position. Post operation, the animal was administrated intramuscularly with 0,8 ml of long acting amoxicillin (Longamox), continued with amoxicillin and clavulanic acid (Claneksi Forte) with 2 x 2 ml as given dosage for 10 days after surgery and Meloxicam tab 7,5mg with 1 x 0,8 mg  as given dosage for 5 days after surgery.